2005
DOI: 10.1021/ic0483895
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Emission Properties of Er3Q9 (Q = 8-Quinolinolate)

Abstract: We report the first combined optical and structural investigation of the water free Er-quinolinolate complex, an organo-lanthanide system of interest for 1.5-microm telecom applications. Structural data demonstrate that the complex has a trinuclear structure (Er3Q9) which provides the Er metals with an octa-coordination by the organic ligand and prevents solvent and water molecules from entering the lanthanide coordination sphere. The results of the structural analysis allow us to infer that the strong Er lumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
74
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 13 publications
(20 reference statements)
6
74
0
Order By: Relevance
“…We have performed this analysis in Er-quinoline complexes, for which detailed x-ray studies have been reported. 7,13 The comparative study confirms that Eq. ͑4͒ just leads to a negligible underestimation, ϳ10%, of the exact dipole-induced transfer rate, calculated using Eq.…”
Section: ͑2͒supporting
confidence: 75%
See 2 more Smart Citations
“…We have performed this analysis in Er-quinoline complexes, for which detailed x-ray studies have been reported. 7,13 The comparative study confirms that Eq. ͑4͒ just leads to a negligible underestimation, ϳ10%, of the exact dipole-induced transfer rate, calculated using Eq.…”
Section: ͑2͒supporting
confidence: 75%
“…m-terphenyl-based ͑L͒ Er 3+ complexes ͑ErL͒ and Er-8-hydroxiquinoline ͑Er 3 Q 9 ͒ in the solid state, for which the necessary optical and structural data are available. In ErL, r =1/k r = 4 ms, 2 R min = 3.7 Å, and ͗␣ A ͘ Er ϳ 6.6 cm −1 ; 15,16 assuming a refraction index n ϳ 1.5, the continuum model yields nr =1/k nr ϳ 0.4 s, in good agreement with the measured NIR lifetime, 0.5 s. 2 In Er 3 Q 9 , r = 5 ± 0.5 ms, 17 R min = 3.4 Å, 13 and ͗␣ A ͘ Er = 1 ± 0.3 cm −1 . 18 With these parameters and for n ϳ 1.5, the theoretical nonradiative lifetime becomes nr ϳ 2.6 s, in very good agreement with the experimental emission lifetime, 2.3 s. 13 As predicted by the continuum model, the previous analysis shows that the larger the vibrational absorption at 1530 nm, the faster the nonradiative decay rate of the rareearth complexes.…”
Section: ͑2͒supporting
confidence: 62%
See 1 more Smart Citation
“…Materials synthetic procedures, chemical, structural and photophysical charaterization are described in recent reports. 5,6 The molecular structures of ErClQ 4 and Er 3 Q 9 are shown in Figure 1.…”
mentioning
confidence: 99%
“…Erbium lifetimes (τ), ∼2 μs in both complexes (see Table 1), have been previously ascribed to nonradiative deactivation induced by C-H stretching vibrations. 5,6 As a first step to determine Er III sensitization efficiency, we measure the quantum yields (Φ IR ) of the Er III IR emission by the relative method using tris(2,2 0 -bipyridyl)ruthenium(II) ion (Ru(bipy) 3 2þ ; 2.40 Â 10 -3 M) in deaerated water as the reference standard (Φ R = 4.2%, τ = 0.58 μs). 7 The quantum yields is determined as…”
mentioning
confidence: 99%